2019
DOI: 10.3390/su11195506
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Stress Testing for China’s Overseas Coal Power Investment Project

Abstract: The advance of the Chinese “Belt and Road” initiative encourages increased overseas investment in coal power projects. However, it also brings about external environmental risks. In this paper, we use the approach of environmental stress testing to examine China’s overseas coal power investment projects by focusing on two countries: Indonesia and Vietnam. We first identify five key testing factors (i.e., coal price, utilization hours, exchange rate, carbon tax, and environmental protection requirements) by exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 15 publications
(18 reference statements)
0
6
0
Order By: Relevance
“…However, China's strategic Belt and Road strategy allows the country to allocate carbon-producing ventures to the BRI associate countries. This has been evident from the fact that almost 65% of the energy-intensive investment within the BRI scheme is planned for coal power projects (Xiong et al 2019). The portion of the fund for clean energy production is found to be extremely negligible.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…However, China's strategic Belt and Road strategy allows the country to allocate carbon-producing ventures to the BRI associate countries. This has been evident from the fact that almost 65% of the energy-intensive investment within the BRI scheme is planned for coal power projects (Xiong et al 2019). The portion of the fund for clean energy production is found to be extremely negligible.…”
Section: Literature Reviewmentioning
confidence: 99%
“…China is on the way to establishing 240 coal energy power projects in 25 BRI associate nations. Moreover, the country intends to establish 92 more such plants in 27 other BRI countries (Xiong et al 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…This inefficient, pollution-intensive coal power increases the social cost of Chinese foreign power plants, which is US$29.7 billion annually, even by conservative estimates (Gallagher, 2018a). By contrast, NDCs to the Paris Agreement encourage host countries to prop up environmental pressures on foreign coal power investments (Xiong et al, 2019). It is argued that an increasing number of coal power projects have been opposed by fierce local protests and raised political debates, causing substantial delays and cancellations (Boulle, 2019;Vidal, 2016).…”
Section: Akihisa Morimentioning
confidence: 99%
“…Ma established an indicator system for country evaluation based on the four aspects of coal reserves, consumption, production and trade in BRI, and proposed a list of major coal investment countries [13]. Taking Vietnam and Indonesia as examples, using the method of environmental stress testing to study China's overseas coal power investment projects, it is found that the coal price and exchange rate are the most sensitive economic factors for Vietnam and Indonesian's coal power projects respectively [14]. Wang used China's foreign trade data of minerals to construct a trade gravity model to evaluate the minerals investment in BRI, and came up with the country's ranking [15].…”
Section: Introductionmentioning
confidence: 99%